Reception Centers and Practices for Women Migrants [version 2; peer review: 2 approved] - Marie Ruiz; Stellamarina Donato (Open Research Europe)
This paper focuses on reception centers for women migrants from a gender mainstreaming perspective and it reflects on the current practices and their adequacy with women migrants’ needs. Based on COST Action Women on the Move (CA19112)’s experience and research, it discusses the different typologies of reception facilities, and highlights the impact of reception on women migrants’ integration, as well as the necessity to coordinate best practices across Europe and EU Member States. Then authors recommend to improve the quality of reception with better trained staff and measures adequate to women migrants’ specific needs for their safety and health. The research also suggests introducing integrative programs and coordinating information and good practices across Europe, but above all an end to detention centers for migrants.